2023
DOI: 10.1021/acsphotonics.3c00951
|View full text |Cite
|
Sign up to set email alerts
|

Hot Electrons and Electromagnetic Effects in the Broadband Au, Ag, and Ag–Au Nanocrystals: The UV, visible, and NIR Plasmons

Alina Muravitskaya,
Artur Movsesyan,
Oscar Ávalos-Ovando
et al.

Abstract: Energetic and optical properties of plasmonic nanocrystals strongly depend on their sizes, shapes, and composition. Whereas the use of plasmonic nanoparticles in biotesting has become routine, applications of plasmonics in energy are still early in development. Here, we investigate hot-electron (HE) generation and related electromagnetic effects in both mono-and bimetallic nanorods (NRs) and focus on a promising type of bimetallic nanocrystal−core− shell Au−Ag nanorods. The spectra of the NRs are broadband, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Hot electrons are typically generated near the surface of the metal and can be injected into adsorbed molecules at the interface between the silver disk and the SiO 2 layer. To quantitatively describe hot electron generation, here, we calculate the generation rate of hot electrons as , rate HEG = 1 4 2 π 2 e 0 2 E normalF 2 false( ω normalΔ E b false) false( ω ) 4 false| E | 2 normald S where e 0 means electron charge, E F denotes the Fermi energy of metal, ℏ is the reduced Planck constant, and ω is the photon angular frequency. The term Δ E b , understood as an energy barrier, may represent not just the height of the electronic barrier between the plasmonic material and the semiconductor contact but also the energy gap between the Fermi level and the level of adsorbed molecules. , In this work, we set Δ E b = 1 eV as a typical energy difference for molecules that can be attached to the metal–dielectric interface.…”
Section: Resultsmentioning
confidence: 99%
“…Hot electrons are typically generated near the surface of the metal and can be injected into adsorbed molecules at the interface between the silver disk and the SiO 2 layer. To quantitatively describe hot electron generation, here, we calculate the generation rate of hot electrons as , rate HEG = 1 4 2 π 2 e 0 2 E normalF 2 false( ω normalΔ E b false) false( ω ) 4 false| E | 2 normald S where e 0 means electron charge, E F denotes the Fermi energy of metal, ℏ is the reduced Planck constant, and ω is the photon angular frequency. The term Δ E b , understood as an energy barrier, may represent not just the height of the electronic barrier between the plasmonic material and the semiconductor contact but also the energy gap between the Fermi level and the level of adsorbed molecules. , In this work, we set Δ E b = 1 eV as a typical energy difference for molecules that can be attached to the metal–dielectric interface.…”
Section: Resultsmentioning
confidence: 99%
“…1–10 These HCs can be transferred to chemically attached acceptors like molecules, which, when properly extracted, could increase the efficiency of various processes and devices like solar cells, water splitting, and photocatalysis. 11–20 For instance, Mukherjee and colleagues demonstrated that challenging chemical reactions like H 2 molecule dissociation on Au surfaces can be initiated by hot electrons (HEs). 21 The energy distribution of HCs can be tuned relative to the size, shape, and elemental composition of the nanostructure.…”
Section: Introductionmentioning
confidence: 99%